Yeatsian Shades In Ó Direáin and Macgill-Eain - Mac Giolla Léith, Caoimhín (Scottish Studies, 2017)
Michael Hartnett’s grandiloquent valediction ‘A Farewell to English’, first delivered from the stage of the Peacock Theatre in Dublin in 1974, announced the thirty-three year-old poet’s decision to cease publishing in his native English, the language in which he had already earned a considerable reputation, in order to devote himself henceforth to poetry in Irish.